2022
DOI: 10.1039/d2ra02803d
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale mapping of temperature-dependent conduction in an epitaxial VO2 film grown on an Al2O3 substrate

Abstract: We investigated temperature-dependent nanoscale conduction in an epitaxial VO2 film grown on an Al2O3 substrate using conductive-atomic force microscopy and deep data analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Vanadium oxide (VO 2 )-based memristive devices are one of the promising classes of materials in the field of artificial neurons. These artificial neurons leverage the unique property of VO 2 to emulate the nonlinear dynamics of biological neurons, which is the metal–insulator transition (MIT) and quick relaxation in response to external stimuli such as electrical pulses . In the past decade, a great deal of research effort has been devoted to understanding the electrically induced MIT in VO 2 thin films on both crystalline and amorphous substrates (Al 2 O 3 , TiO 2 , Si, SiO 2 , Ge, Ti, Pt, and TiN). The MIT in VO 2 thin films have been well achieved on many different substrates, which makes this material particularly appealing for developing CMOS-compatible artificial neurons . For instance, Yi et al demonstrated that the sputter-deposited Pt/VO 2 /Pt devices on Si 3 N 4 /Si substrates achieve several biological neuronal dynamics with a superior energy efficiency of >10 13 spikes/J …”
Section: Introductionmentioning
confidence: 99%
“…Vanadium oxide (VO 2 )-based memristive devices are one of the promising classes of materials in the field of artificial neurons. These artificial neurons leverage the unique property of VO 2 to emulate the nonlinear dynamics of biological neurons, which is the metal–insulator transition (MIT) and quick relaxation in response to external stimuli such as electrical pulses . In the past decade, a great deal of research effort has been devoted to understanding the electrically induced MIT in VO 2 thin films on both crystalline and amorphous substrates (Al 2 O 3 , TiO 2 , Si, SiO 2 , Ge, Ti, Pt, and TiN). The MIT in VO 2 thin films have been well achieved on many different substrates, which makes this material particularly appealing for developing CMOS-compatible artificial neurons . For instance, Yi et al demonstrated that the sputter-deposited Pt/VO 2 /Pt devices on Si 3 N 4 /Si substrates achieve several biological neuronal dynamics with a superior energy efficiency of >10 13 spikes/J …”
Section: Introductionmentioning
confidence: 99%